A Pocket Guide to Sharks of the World Second Edition - Ebert, David A. (Princeton University Press, 2021)
An updated and comprehensive guide identifying all of the world's sharksSharks are some of the most misunderstood animals on the planet. We still have a lot to learn about these fascinating creatures, which are more seriously threatened with extinction and in greater need of conservation and management than any other major group of vertebrates.A Pocket Guide to Sharks of the World is the only field guide to identify, illustrate, and describe every known shark species. Its compact format makes it handy for many situations, including recognizing living species, fishery catches, or parts sold at markets. This expanded second edition presents lavish images, details on newly discovered species, and updated text throughout. The book contains useful sections on identifying shark teeth and the shark fins most commonly encountered in the fin trade, and takes a look at shark biology, ecology, and conservation. A Pocket Guide to Sharks of the World will be an essential resource and definitive reference for years to come.An updated guide to all of the world's sharksEach species is illustrated and describedHandy, compact format with concise textUseful sections on the identification of shark teeth and fins
Description based on online resource; title from PDF title page (publisher's Web site, viewed 30. Aug 2021)
Keywords: NATURE / Animals / Marine Life; Sharks -- Identification